Can Corporate Social Responsibility Promote Employees’ Taking Charge? The Mediating Role of Thriving at Work and the Moderating Role of Task Significance - Yan, Aimin; Tang, Liping; Hao, Yingchun (Frontiers in Psychology, 2021)
Based on the theory of resource conservation, this study discusses the influence mechanism of corporate social responsibility (CSR) on employee taking charge, as well as the mediating role of thriving at work and the moderating role of task significance. The research hypotheses were tested by using the conditional PROCESS analysis based on a survey of 444 employees in China, and the results of empirical analysis show that: (1) CSR is positively related to employee taking charge; (2) thriving at work plays an mediating role in the relationship between CSR and employee taking charge; (3) task significance negatively moderates the relationship between CSR and employee thriving at work, which is weaker when task significance is high. (4) Task significance negatively moderates the mediating effect between CSR and employee taking charge, such that the lower the task significance, the greater the effect of CSR on taking charge via thriving.